Efektivitas Perawatan Luka Dengan Metode Perawatan Luka Modern Dan Perawatan Luka Konvensional Pada Pasien Diabetes Melitus - Colin, Vellyza; Listiana, Devi (Universitas Tribhuwana Tunggadewi, 2022)
Diabetic ulcers are chronic complications of Diabetes Mellitus, which are open sores on the skin surface accompanied by local tissue death. The purpose of this study was to determine the effectiveness of modern wound care methods and conventional wound care for diabetic ulcers. The design of this study was pre-experimental with a two-group pre-and post-test design approach. The population was 60 respondents recruited with a purposive sampling technique. The study was conducted at the Rafflesia Wound Care Clinic by using modern wound care methods (30 people) the drugs used in modern wound care are Hydrocolloid, Honey, Treebe, Metkovazin, TTO Serum, Stero-bac, Calcium Alginate, NaCl. At the dr. M. Yunus Bengkulu General Hospital by using conventional wound care methods (30 people), while the conventional method only uses NaCl, Metkovazin, and gauze. The wound healing process was assessed using the Bates Jensen Wound Assessment Tool observation sheet. The study was conducted on September 1-30 2020. The results of wound conditions before and after treatment using modern dressing techniques in diabetic ulcer patients showed two free samples F = 1.347 with p-value = 0.251 0.05, T = 0.626 with p-value = 0.534 0.05. In conclusion, diabetic wound healing using modern and conventional methods has the same effect, however modern wound care is better in healing time.